A new method for studying platelets, based upon the low-angle light scattering technique. 1. Theoretical and experimental foundations of the method. Issue 5 (2005) - Mindukshev Mindukshev, Igor V. Igor V.; Jahatspanian Jahatspanian, Igor E. Igor E.; Goncharov Goncharov, Nikolay V. Nikolay V.; Jenkins Jenkins, Richard O. Richard O.; Krivchenko Krivchenko, Alexander I. Alexander I.
Abstract : A new method is presented for simultaneous monitoring of changes in shape and aggregation of platelets. The signal of light scattering alterations at angles below six degrees was shown to be determined by platelet aggregation dynamics (aggregation, disaggregation, coagulation). Over a range of larger angles (6–15 degrees), cell shape changes also contributed to the signal: (i) spherization, and (ii) pseudopodia formation. The first stage was shown to be fast ( t 1/2 of few seconds) and correlated with [Ca 2+ ] increase. It was characterised by a narrow signal fluctuation and by a rapid increase (30–40%) in signal intensity. During the second stage, which was much slower, the signal decreased describing the aggregation process. The EC50 value for ADP-induced spherization was 40 nmol l –1 . Aggregation kinetics in saline solution under turbulent flow showed second order kinetics in relation to initial cell concentration. The rate constant depended on stirring conditions and on calcium concentration in the medium. Standardisation of the testing conditions made it possible to characterize the initial functional state of platelets by their sensitivity to agonists, with estimation of EC50 and maximum velocity of aggregation ( U max ) values. The method has potential applications in pharmacology and toxicology research and in clinical practice, as a simple and highly sensitive functionality test for platelets.